Every bit a cowboy - Marts, Jennie (Marts, Jennie. Creedence Horse Rescue., 2023)
When her building floods, divorced hairdresser Carley Chapman is forced to temporarily move her salon out to the Heaven Can Wait Horse Rescue Ranch where she finds herself drawn to deputy sheriff and cattle rancher Knox Garrison who does the unexpected when her no-good ex starts causing trouble.